17th AIAA/CEAS Aeroacoustics Conference (32nd AIAA Aeroacoustics Conference) 2011
DOI: 10.2514/6.2011-2884
|View full text |Cite
|
Sign up to set email alerts
|

Large-Eddy Simulations of a Supersonic Heated Jet

Abstract: Large-eddy simulations of imperfectly expanded jet flows from a convergent-divergent nozzle with a heated (600K) and a cold jet conditions have been carried out. Mach wave radiation is present outside the jet core and the heated jet shows a much larger density shear-layer spreading than the cold jet. The potential core length is shortened, but the shock-cell shape and shock-cell spacing remain similar to those shown in the cold jet. It is found that the Crocco-Busemann equation captures well the correlation be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The flow structure and acoustics of these conic convergent-divergent nozzles have been presented elsewhere [13] in detail and will not be repeated here. In more recent work, our simulations have been extended to include the effects of inflow turbulence [14] and jet heating [10], since realistic operating conditions involve hot turbulent, exhaust jets. The results from the simulations of heated jets are in agreement with observations made in the literature.…”
Section: B Representative Engine Nozzles To Explore Multi-stream Conmentioning
confidence: 99%
See 1 more Smart Citation
“…The flow structure and acoustics of these conic convergent-divergent nozzles have been presented elsewhere [13] in detail and will not be repeated here. In more recent work, our simulations have been extended to include the effects of inflow turbulence [14] and jet heating [10], since realistic operating conditions involve hot turbulent, exhaust jets. The results from the simulations of heated jets are in agreement with observations made in the literature.…”
Section: B Representative Engine Nozzles To Explore Multi-stream Conmentioning
confidence: 99%
“…An AIAA journal paper addressing verification and validation of supersonic jet exhaust flows has been published [3]. Previous studies have looked at the effect of exhaust temperatures on flow instabilities [2,10], the impact of some flow modifiers on engine performance and noise from supersonic rectangular jets [1] and the effectiveness of various noise reduction techniques [18,19,22].…”
Section: Introductionmentioning
confidence: 99%
“…Song et al [19] have established a simulation model of jet flow of a carrier-borne aircraft, studied the influence of high temperature, high speed and high pressure jet flows on the guide plate under different deflection angles, and compared the simulation results with the experimental results. Liu et al [20], [21] have studied the impact of a typical aircraft carrier deck and jet blast deflector (JBD) under the condition of under-expansion air flow with finite element method. Sun et al [22] have analyzed the influence of jet flow of a carrier on the wind field, velocity field and pressure field on the deck based on the theory of computational fluid dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Liu, et al [130] have observed that, although inflow forcing causes the turbulence levels to rise faster close to nozzle exit, its impact is much smaller further downstream. They also noted a reduction in screech amplitude due to inflow forcing.…”
Section: Initial and Boundary Conditionsmentioning
confidence: 99%